The Next Ten Years: Looking Back, Looking Forward - Glass, Chris R; Bista, Krishna (Journal of International Students, 2019)
As we near our tenth year as a publication, the journal’s global community continues to grow in ways we could not have imagined when we first started. We now receive over 300 submissions per year. We are proud to be among the top-20 journals in higher education according to GoogleScholar with almost 10,000 active subscribers around the world. As we prepare for the next ten years, we want to share a few updates on where we have been and where we are going. We have five major focus areas as we move forward as a publication: expand our global network of authors, scholars, and leaders; design top-tier journal design and seamless editorial workflow; build international partnerships and diversity editorial team; create mentor pathways for emerging scholars; and develop sustainable funding and support.